Growth Types and Bonding Mechanisms for Copper / Steel Interface by Fusion Welding (University of Thi-Qar Journal for Engineering Sciences, 2011)
The aim of this work is to study the possibility of joining copper ( ASTM , C1020100 ) to low carbon steel ( ASTM A36 ) using the shielded metal arc welding ( SMAW ) and the gas tungsten arc welding ( GTAW ) processes by eight types of electrodes ; ERNiCrFe-5 , ERNiCu-7 , ECu , ECuSn-A, E309L, E 312, E7018 , and ENi-1. Joint is designed as single –V – butt weld for 5 mm thickness plate . From the microstructure observation there were two kinds of boundaries ; the first is homogenous weld , which happens when fillers with chemical composition is similar to those of one of the parent metals . While the second type is heterogenous nucleation , which happens when the chemical compositions of the fillers and the parent metals are not similar . Three types of solidification were regonized ; the first is epitaxial from the copper side , the second is nonepitaxial from the steel side , and the third type is competitive which shown in the two sides . Solidification cracks on the steel side are shown , and these cracks are filled by brazing process . All tested specimens in tension and bending show the copper properties .